Inappropriate supplementation of Vitamin D can result in toxicity: a cross-sectional study of paediatrics population - Shamim, Nazia; Majid, Hafsa; Khemani, Suneeta; Salim, Maliha; Muneer, Siraj; Khan, Aysha Habib (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate children with suspected or definite hypervitaminosis D with respect to prevalence, clinical manifestations and pharmacological aspects. Method: The retrospective cross-sectional study was conducted at the Aga Khan University Hospital, Karachi, and comprised medical records from January 1 to December 31, 2018, of children aged <18 years with 25-hydroxyvitamin D levels >50ng/ml. Clinical and pharmacological data was retrieved. Data was analysed using SPSS 23. Results: Of the 118,149 subjects visiting the clinical laboratory during the study period, children tested for serum 25-hydroxyvitamin D levels were 16,316(13.8%) who had a median age of 9.78 years (interquartile range: 10.2 years). Children who registered for consultation were 2720(16.6%), and, out of them, 602(22%) had serum 25-hydroxyvitamin D >50ng/ml. The median 25-hydroxyvitamin D levels and age were 70.1ng/ml (interquartile range: 100ng/ml) and 3.1 years (interquartile range: 17.93 years), respectively, and 345(57.3%) of them were boys. Children supplemented with vitamin D were 197(33.1%) and 193(97.9%) of them were prescribed by physicians. Mega-doses were taken by 68(34.17%), while the remaining had used various combinations in syrup or tablet forms. Commonly prescribed mega-doses were 600,000IU 30((44.1%) and 200,000IU 31(45.5%) injections of vitamin D. The primary indications were pains/aches in 51(25.8%) cases, developmental delay 50(25.3%), and vitamin D deficiency 49(24.8%). The main symptoms of hypervitaminosis D or toxicity were abdominal pain 27(13.7%) and constipation 31(15.7%). Conclusions: Children should be given vitamin D supplements with caution as prolonged supplementation and repeated mega-doses can result in toxicity which may cause serious consequences. Key Words: Vitamin D deficiency, Vitamin D supplements, Hypervitaminosis D, Vitamin D toxicity.